Working posture analysis on oyster mushroom farmers using OWAS method in Lempake, Samarinda, East Kalimantan - Lina Dianati Fathimahhayati; Theresia Amelia Pawitra; Willy Tambunan; Markus Hartono (Universitas Lancang Kuning, 2021)
A preliminary survey showed that oyster mushroom farmers in Lempake Samarinda experienced pain in several body segments, especially at their waist. It may be attributable to the working condition that requires non-ergonomic postures such as frequent awkward posture in sitting or standing position. Therefore, this paper aims to assess the working posture in oyster mushroom farmers. Ovako Working Posture Analysis System (OWAS) method was applied to measure the risk level of farmers' working posture. A total of ten activities were observed from the oyster mushroom cultivations' process in four cultivations in Lempake, Samarinda, Indonesia. Each activity was assessed using the OWAS category based on the position of the back, arms, legs, and load. The result showed that 10% of farmers' working posture was classified in the 4th risk level category, categorized as highly dangerous for the musculoskeletal system, so direct improvement was needed. Furthermore, 10% of working postures were classified in the 3rd risk level category, and 60% of working posture was in the 2nd risk level category, which is categorized as dangerous for the musculoskeletal system and could cause significant tension so that improvement in the future as needed. On the other hand, 20% of working posture was classified in the 1st category which was safe for the musculoskeletal system